Kata Ganti Nama dan Representasi Identiti Pewacana Parlimen : Pronouns and Identity Representations of Parliamentary Speakers - Dayang Sariah, Abang Suhai; Kesumawati, Abu Bakar; Norsimah, Mat Awal (Universiti Sains Malaysia, 2023)
In a discourse of political interaction, the use of pronouns can indirectly reflect the identity of the speakers involved, specifically the government’s or opposition’s member of parliament. Besides being used to refer to a person, personal pronouns (PP) can describe the form of social relationship built between the speakers and the audience. This study aims to identify the form of the first personal pronoun utilised by government and opposition discourse as well as explain the identity highlighted through the use of PP based on critical discourse analysis approach. The text of the 2019 Budget debate is used as study data. A preliminary review of this study found that in both government and opposition discourse, the use of singular first PP “saya” is dominant compared to the use of plural first PP. For the plural PP, the use of “kita” inclusively is dominant in the opposition, while the the use of “kita” exclusively is dominant in the government. Similarly, both discourses are seen trying to “stand out” on their own, stand up, have a personal touch, and even try to get closer to their target audience. In comparison, the opposition emphasises the nature of belonging and togetherness with its discourse audience, while the government emphasises the nature of party which is seen as trying to strengthen the party’s position as the “new ruler” in the new Malaysian parliament.